Evaporation and Evapotranspiration Measurements and Estimations - Abtew, Wossenu. (Springer Netherlands : Imprint: Springer, 2013)
The book is a thorough presentation of theoretical and applied aspects of the evaporation and evapotranspiration process supported by data from experimental studies. It is written in a way that the theoretical background of evaporation and evapotranspiration estimation is presented in a simplified manner, comprehensive to most technical readers. Part ofthe book deals with details of meteorological parameters and monitoring sensors which are needed for estimating evaporation and evapotranspiration. Errors in meteorological parameter measurements are also presented. Estimation errors, strengths, weaknesses and applicability of a wide range of evaporation and evapotranspiration estimation methods are presented along with samples of application to a certain region. The book presents applications of newer, simpler methods, anda new technology: remote sensing application to evaporation and evapotranspiration estimation. The latest interest in the subject, climate change and evapotranspiration is discussedin the last chapter. This book will be beneficial to students, hydrologists, engineers, meteorologists, water managers and others.